Smart LED Lighting System for Energy Efficient Industrial and Commercial LVDC Nanogrid Powered Buildings with BIPV - Shankar, Ajay; Vijayakumar, K.; Babu, B. Chitti; Durusu, Ali (IEEE, 2020)
Due to rapid urbanization, inclination in the energy demand has been experienced in the recent years which posed the threat of energy security and global warming. Artificial lighting in buildings shares an impactful amount of energy consumption, which needs to be minimize. Semitransparent building integrated photovoltaic (BIPV) cells have the potential of generating clean energy and allowing the daylight harvesting in the building, which can minimize the energy consumption across lighting by a great extent. In this paper opportunities of energy saving across low voltage DC (LVDC) nanogrid powered LED lighting in an industrial building by considering daylight harvesting and BIPV cells has been investigated. Results reflects that a significant amount of energy can be conserved across LED lighting by utilizing BIPV cells which allows daylight through it in the room. Moreover, a notable amount of clean energy can also be generated using semitransparent BIPV cells.
Keywords: LED lighting; daylight harvesting; BIPV; energy saving; zero energy building (ZEB); renewable energy sources (RES); INTEGRATED PHOTOVOLTAIC SYSTEM; PERFORMANCE; Computer Science; Energy & Fuels; Engineering